Soft Skills : How to See, Measure and Build the Skills that Make Us Uniquely Human - Moldoveanu, Mihnea (De Gruyter, 2024)
Although communicative and relational skills are currently in the greatest demand in organizations large and small, we are as educators, executives, and talent developers very far away from the kind of precision in identifying, measuring, selecting and developing these skills that we have achieved with cognitive and technical skills. At the same time, the relentless automation of swaths of human tasks has placed a sharp light on the 'quintessentially human skills' - those that cannot and in some cases should not be subject to algorithmic automation. This book aims to 'change the soft skills game' by introducing language for identifying and describing them, ways of measuring the degree to which a person possesses them and selecting those who possess them in the utmost from those less skilled, and ways of helping students and executives alike develop them, through a methodology that has been designed and practiced for the past ten years. We need a 're-set' in the way we think about human skill and in particular the ways we think about those human skills which cannot be sub-contracted to an algorithm running on silicon. This book aims to provide that re-set.